18F-FDG PET/CT of Primary Extraskeletal Ewing Sarcoma of the Prostate. (6th December 2022) - Guo, Yue-Hong; Yang, Min-Fu
Abstract: Prostate Ewing sarcoma is rare. We report the 18 F-FDG PET/CT finding of a 16-year-old adolescent boy who presented with dysuria and was confirmed to be extraskeletal Ewing sarcoma of the prostate by histopathologic findings.